Isolation and genomic characterization of chicken infectious anemia virus in Jiangsu province of China during 2020–2022 - Zhang, Jun; Ma, Li; Li, Tuofan; Xie, Quan; Wan, Zhimin; Qin, Aijian; Ye, Jianqiang; Shao, Hongxia; Wang, Shengnan (Frontiers in Veterinary Science, 2024)
As an immunosuppressive disease virus, chicken infectious anemia virus (CIAV) mainly infects chickens, causing aplastic anemia and systemic lymphoid tissue atrophy. In recent years, the prevalence of CIAV in the poultry industry globally has caused huge economic losses. In this study, a total of 223 clinical samples, including anal swabs, tissues, blood, and vaccines, were collected from 19 broiler farms or breeding companies in Jiangsu province, with symptoms of significant anemia and immunosuppression during 2020–2022. Among them, 75 samples (75/223, 33.6%) were positive for CIAV in polymerase chain reaction (PCR) test, and 20 CIAV strains were successfully isolated. The phylogenetic trees of the 20 isolates and 42 CIAV strains deposited in GenBank formed four distinct groups (A-D). And the isolates mainly belonged to Group A but with high genetic diversity. Analysis for VP1 indicated that these isolates possess key characteristics of highly pathogenic strains. Meanwhile, VP2 and VP3 were much conserved with much fewer mutations compare to VP1. The above epidemiological study of CIAV provides novel insights into molecular characterization of CIAV and lays the foundation for developing efficient strategies for control of CIAV in China.